GANGLION CELL–INNER PLEXIFORM LAYER THICKNESS IN EYES WITH NONEXUDATIVE AGE-RELATED MACULAR DEGENERATION OF DIFFERENT DRUSEN SUBTYPES. Issue 8 (August 2021) - Nam, Ki Tae; Chung, Hyun Woo; Jang, Sungmin; Hwang, Soon-Young; Kim, Seong-Woo; Oh, Jaeryung; Yun, Cheolmin
Abstract : Purpose: We sought to investigate the ganglion cell–inner plexiform layer (GCIPL) thickness in eyes with nonexudative age-related macular degeneration. Methods: We classified eyes into four categories—pachydrusen, soft drusen, subretinal drusenoid deposit (SDD), and soft drusen with SDD—and compared the baseline mean macular GCIPL thickness according to the Early Treatment Diabetic Retinopathy Study grid and its change between groups. Results: We classified 53, 29, 36, and 34 eyes into the four categories, respectively. The mean GCIPL thickness values in the 3-mm area were 82.61 ± 9.54 µ m for the pachydrusen group, 79.11 ± 10.26 µ m for the soft drusen group, 77.72 ± 6.04 µ m for the SDD group, and 71.63 ± 8.69 µ m for the soft drusen with SDD group ( P < 0.001). The soft drusen with the SDD group showed a greater change in GCIPL thickness (−2.50 ± 0.29 µ m/year) in the 3-mm area as compared with the pachydrusen group (−0.18 ± 0.35 µ m/year), soft drusen group (−0.55 ± 0.36 µ m/year), and SDD group (−0.55 ± 0.37) (all P < 0.001). Conclusion: The GCIPL thickness varied according to the type of nonexudative age-related macular degeneration. The thinner baseline GCIPL and its greater change in eyes with soft drusen with SDD may suggest that these eyes are experiencing more prominent neuroretinal degeneration in the central 3-mm area than those in the other groups. Abstract : Supplemental Digital Content is Available in the Text.Ganglion cell–inner plexiform layer and chorioretinal thickness vary according to the type of drusen in nonexudative age-related macular degeneration eyes.